Current situation of atmospheric nanoparticles in Fukue Island, Japan. Issue 1 (1st January 2018) - Chandra, Indra; Seto, Takafumi; Otani, Yoshio; Inomata, Yayoi; Hama, Naoya; Yoshino, Ayako; Takami, Akinori; Takegawa, Nobuyuki
Abstract: Emissions of polluted air in East Asia have gradually decreased over the last decade. Those air pollutants have been transported over long distances and influenced new particle formation (NPF) in the downstream region. We obtained 5-year data of the mobility size distribution and SO2 and particulate (PM2.5 ) emissions on Fukue Island (32.75°N, 128.68°E), Japan. Frequent NPF events in the 2013 campaign were observed around 60% under the transboundary transport of polluted air by northwesterly wind. In contrast to the data obtained in the last 2-year campaign (2016–2017), these NPF events (<25%) may reflect a relatively clean environment. The daily average SO2 and PM2.5 concentrations over the campaign periods are 2.3 ± 2.2 ppb and 17.6 ± 8.5 µg·m −3 (February 23 to March 7, 2013), 1.3 ± 0.9 ppb and 13.8 ± 4.7 µg·m −3 (February 27 to March 18, 2015), 0.8 ± 0.5 ppb and 14.7 ± 5.3 µg·m −3 (February 27 to March 25, 2016), and 0.5 ± 0.5 ppb and 12.1 ± 4.6 µg·m −3 (January 28 to April 19, 2017), respectively. These reductions of emissions may be due to the measures implemented by the local government in the source region to handle the adverse impacts of environmental pollution. The latest condition of atmospheric nanoparticles on Fukue Island can be used as an indicator to determine the concentration levels of regional air pollutants in East Asia.